2015
DOI: 10.1016/j.jcz.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Penile histomorphology of the neotropical bat Eptesicus furinalis (Chiroptera: Vespertilionidae)

Abstract: External and internal penile morphologies have evolved rapidly and divergently in many mammalian orders and are extremely useful for taxonomic studies, particularly in the recovery of phylogenetic relationships. Eptesicus furinalis, a Vespertilionid bat, belongs to a taxon in which species recognition can be difficult when only traditional features are employed. Therefore, any feature that may contribute to the more accurate characterization of this taxon is relevant. In this study, we describe the histomorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 41 publications
4
10
1
Order By: Relevance
“…Unlike the condition observed in some genera of vespertilionid bats (Herdina et al, 2010;Comelis et al, 2015) where the corpora cavernosa are not part of the glans (which contains mostly accessory cavernous tissue) and for humans who do not have accessory tissue in the penis (Yiee and Baskin, 2010), both corpora cavernosa and accessory cavernous tissue are present in the glans penis of all species of molossids analyzed thus far, except for Moormopterus planiceps where Krutzsch and Crichton (1987) were unable to find this tissue. This fact supported the Smith and Madkour (1980) proposition that the absence or reduction of these tissues in bats is a derived condition.…”
Section: Discussioncontrasting
confidence: 62%
See 4 more Smart Citations
“…Unlike the condition observed in some genera of vespertilionid bats (Herdina et al, 2010;Comelis et al, 2015) where the corpora cavernosa are not part of the glans (which contains mostly accessory cavernous tissue) and for humans who do not have accessory tissue in the penis (Yiee and Baskin, 2010), both corpora cavernosa and accessory cavernous tissue are present in the glans penis of all species of molossids analyzed thus far, except for Moormopterus planiceps where Krutzsch and Crichton (1987) were unable to find this tissue. This fact supported the Smith and Madkour (1980) proposition that the absence or reduction of these tissues in bats is a derived condition.…”
Section: Discussioncontrasting
confidence: 62%
“…When comparing results of the evaluated Molossidae taxa with those of Vespertilionidae already analyzed (Wimsatt and Kallen, 1952;Comelis et al, 2015;Herdina et al, 2015a,b), we found that this condition was additionally observed for some vespertilionid taxa. However, data for Eptesicus furinalis revealed that the penis corpus spongiosum is well developed in this taxon (Wimsatt and Kallen, 1952;Comelis et al, 2015), indicating that there is, in this family and more specifically in this taxon, a derived condition for this character.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations